MODEL EDUKASI GIZI DENGAN MEDIA BUKU MEWARNAI UNTUK SISWA PAUD DI KELURAHAN OEBA: MODEL EDUKASI GIZI DENGAN MEDIA BUKU MEWARNAI UNTUK SISWA PAUD DI KELURAHAN OEBA - Juni Gressilda Louisa Sine (Kupang Journal of Food and Nutrition Research, 2021)
Nutrition education should start at an early age to build healthy eating patterns or habits. The most effective education is given to children aged two to six years. This education is not only carried out at home, but also in educational institutions, including at an early age. Coloring books are one of the educational media that can be used to apply nutritional knowledge to children aged 2-6 years. The purpose of this study was to find out that the nutritional education model with coloring book media could increase the knowledge of nutrition in early childhood. The design of this research is a qualitative study which was analyzed with a descriptive approach. This research was conducted at Early Childhood Education in Kelurahan Oeba. The subjects of the study were early childhood students aged 5-6 years as many as 13 people. In addition, this research also involved the parents of early childhood students and early childhood teachers. Types and sources of data used are sourced from primary data and secondary data. Primary data was obtained from observations and direct interviews with parties related to the field of research. Secondary data is obtained from supporting data for Early Childhood Education. The nutritional knowledge of PAUD participants became better after the provision of nutrition education materials with coloring books. PAUD students' knowledge of the types and functions of nutrients is better after receiving nutritional material through the coloring books that have been developed. Coloring books can be used as an educational medium to increase children's nutritional knowledge by coloring pictures of food based on their nutritional group. Coloring books can be an alternative to teacher handbooks in early childhood education in increasing knowledge of early childhood nutrition that can be included in the existing curriculum. Coloring books should not be all in the form of pictures, but given descriptions of pictures in the form of writing. It is intended that children can simultaneously learn letter recognition and reading.